L’intentionnalité et le projet professionel: préalables conceptuels de recherche - Drolet, Jean-Louis (Canadian Journal of Counselling and Psychotherapy, 2011)
This study presents the significant manner in which the existential concept of intentionality can contribute to a better understanding of the relationship between the individual and work. The author examines certain basic postulates considered prerequisites to a further investigation into intentionality as it is expressed through the professional project. Intentionality is differentiated from intention and is defined here as a dynamic, ultimate structure of meaning that the individual expresses through his dialectical rapport with his environment